Incorporating the effect of the photon spectrum on biomass accumulation of lettuce using a dynamic growth model - Abedi, Mahyar; Tan, Xu; Stallknecht, Eric J.; Runkle, Erik S.; Klausner, James F.; Murillo, Michael S.; Bénard, André (Frontiers in Plant Science, 2023)
Cultivation studies in specialty crop optimization utilize models to estimate the fresh and dry mass yield. However, the spectral distribution and photon flux density (µmol m-2 s-1) affect plant photosynthetic rate and morphology, which is usually not incorporated in plant growth models. In this study, using data for indoor-grown lettuce (Lactuca sativa) cultivated under different light spectra, a mathematical model that incorporates these effects is presented. Different experimental cases are used to obtain a modified quantum use efficiency coefficient that varies with spectral distribution. Several models for this coefficient are fitted using experimental data and obtained values. Comparing the accuracy of these models, a simple first- or second-order linear model has about 6 to 8 percent uncertainty, while a fourth-order model has a 2 percent average error in prediction. In addition, normalizing overall spectral distribution leads to a more accurate prediction of the investigated parameter. A mathematical model based on normalized spectral irradiance integrated over wavelength for photosynthetically active radiation (PAR) wavebands and the far-red waveband is presented in this study that accurately predicts lettuce dry mass grown indoors under different light spectra.